Molecular cloning of the region of the terminus of Escherichia coli K-12 DNA replication. - Béjar, S (1983)
A series of plasmids have been isolated either by ligation of defined restriction fragments to plasmid pBR325 or by screening of a cosmid bank by in situ colony hybridization. Together with one previously isolated plasmid, they spanned 86% of the 30.5- to 34-min region of the genetic map of Escherichia coli K-12. Physical analysis of these plasmids and hybridizations to Southern blots confirmed the endonuclease map of this region, with the exception of a 9.3-kilobase pair inversion.